Creative pedagogy in action: Character-based social campaign media for teacher preparation - Setiawan, Anjar; Hayati, Mardiyan; Mulyadi, Dodi; Wijayatiningsih, Testiana Deni (Universitas Jambi, Indonesia, 2026)
This study explores the use of creative pedagogy in helping pre-service teachers develop creative thinking and communication skills through a social campaign poster project. The participants were 41 fifth-semester students from the English Education program at Universitas Muhammadiyah Semarang. In this study, students identified social or educational issues and created persuasive posters that reflected values such as empathy, responsibility, cooperation, and ethics. Data were collected through observation, poster evaluation, and reflective questionnaires. The assessment focused on fluency, flexibility, originality, and elaboration aspects of creative thinking. The results showed that students performed well in fluency and elaboration. However, flexibility and originality were lower, suggesting that students still need more support in developing visual literacy and divergent thinking. The activity also encouraged students to see themselves as future teachers who communicate ethically. Overall, the findings suggest that project-based activities can help students improve both communication skills and awareness of educational values.